Lewy bodies in grafted neurons in subjects with Parkinson's disease suggest host-to-graft disease propagation - Li, Jia-Yi; Englund, Elisabet; Holton, Janice L; Soulet, Denis; Hagell, Peter; Lees, Andrew J; Lashley, Tammaryn; Quinn, Niall P; Rehncrona, Stig; Björklund, Anders; Widner, Håkan; Revesz, Tamas; et al. (Nature medicine, 2008)
Two subjects with Parkinson's disease who had long-term survival of transplanted fetal mesencephalic dopaminergic neurons (11–16 years) developed α-synuclein–positive Lewy bodies in grafted neurons. Our observation has key implications for understanding Parkinson's pathogenesis by providing the first evidence, to our knowledge, that the disease can propagate from host to graft cells. However, available data suggest that the majority of grafted cells are functionally unimpaired after a decade, and recipients can still experience long-term symptomatic relief.